Progressive Massive Choroidal Neovascularization: A Severe Phenotype of Refractory Neovascular Age-Related Macular Degeneration. (May 2017) - Cheung, Albert Y.; Rao, Prethy; Yonekawa, Yoshihiro; Thomas, Benjamin J.; Shah, Aparna; Garretson, Bruce R.; Capone, Antonio; Hassan, Tarek S.
Purpose: A small subset of patients with neovascular age-related macular degeneration (AMD) can have relentless progression of choroidal neovascularization (CNV) and subsequent disciform scarring (DS) with extension beyond the vascular arcades to the equator. We present the clinical courses of this severe phenotype of progressive massive CNV (PM-CNV). Methods: Retrospective case series of 14 eyes of 8 patients who presented with (1) massive DS encompassing the posterior pole and extending to the equator and (2) progressive DS expansion despite treatment between 2004 and 2015 at a tertiary referral center. Demographics, clinical and ocular characteristics, fluorescein angiographic findings, and treatment regimens were reviewed. Results: Baseline characteristics included a mean age of 73.0 years (range, 65.- 86.9 years) with 7 (87.5%) women. Six (75%) patients had bilateral PM-CNV. Mean follow-up was 10.5 years (range, 0.5-18.2 years). Ten (71.4%) eyes underwent intravitreal anti-vascular endothelial growth factor therapy, 3 (21.4%) intravitreal corticosteroid injections, and 3 photodynamic therapy. Most eyes (92.9%) demonstrated subretinal hemorrhage at the edge of the DS prior to DS expansion during treatment. Of the 6 patients with bilateral PM-CNV, 5 developed DS in 1 eye earlier than the subsequent eye (mean time, 63.6 months). Final visual acuity was ≤20/400 in all eyes (20/400 [n = 1]), count fingers (n = 5), hand motions (n = 5), and no light perception (n = 3). Conclusion: Progressive massive CNV is a profound reactivation of DS in some AMD eyes and is associated with severe, often bilateral, vision loss.